Identification of the lncRNA–miRNA‒mRNA regulatory network for middle cerebral artery occlusion-induced ischemic stroke - Shi, Guixin; He, Dong; Xiao, Hua; Liu, Yu’e; Liu, Chuanyong; Cao, Fang (Frontiers in Genetics, 2023)
Stroke known as a neurological disease has significant rates of disability and mortality. Middle cerebral artery occlusion (MCAO) models in rodents is crucial in stroke research to mimic human stroke. Building the mRNA and non-conding RNA network is essential for preventing MCAO-induced ischemic stroke occurrence. Herein, genome-wide mRNA, miRNA, and lncRNA expression profiles among the MCAO group at 3h, 6h, and 12h after surgery and controls using high-throughput RNA sequencing. we detected differentially expressed mRNAs (DE-mRNAs), miRNAs (DE-miRNAs), and lncRNAs (DE-lncRNAs) between the MCAO and control groups. In addition, biological functional analyses were conducted, including GO/KEGG enrichment analysis, and protein-protein interaction analysis (PPI). GO analysis indicated that the DE-mRNAs were mainly enriched in several important biological processes as lipopolysaccharide, inflammatory response, and response to biotic stimulus. The PPI network analysis revealed that the 12 DE-mRNA target proteins showed more than 30 degree with other proteins, and the top three proteins with the highest node degree were Alb, IL-6, and TNF. In the DE-mRNAs, we found the mRNA of Gp6 and Elane interacting with two miRNAs (novel_miR_879 and novel_miR_528) and two lncRNAs (MSTRG.348134.3 and MSTRG.258402.19). As a result of this study, a new perspective can be gained into the molecular pathophysiology leading to the formation of MCAO. The mRNA-miRNA‒lncRNA regulatory networks play an important role in MCAO-induced ischemic stroke pathogenesis and could be applied to the treatment and prevention of ischemic stroke in the future.